2024
DOI: 10.1186/s12870-024-05292-1
|View full text |Cite|
|
Sign up to set email alerts
|

Seed priming with potassium nitrate alleviates the high temperature stress by modulating growth and antioxidant potential in carrot seeds and seedlings

Muhammad Mahmood ur Rehman,
Jizhan Liu,
Aneela Nijabat
et al.

Abstract: Early season carrot (Daucus carota) production is being practiced in Punjab, Pakistan to meet the market demand but high temperature hampers the seed germination and seedling establishment which cause marked yield reduction. Seed priming with potassium nitrate breaks the seed dormancy and improves the seed germination and seedling growth potential but effects vary among the species and ecological conditions. The mechanism of KNO3 priming in high temperature stress tolerance is poorly understood yet. Thus, pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors identified an error in the Acknowledgement and Funding sections. The corrections are highlighted in bold.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the Acknowledgement and Funding sections. The corrections are highlighted in bold.…”
mentioning
confidence: 99%